1996
DOI: 10.1016/s0014-5793(96)01192-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein phosphatases induces IGF‐1‐blocked neurotrophin‐insensitive neuronal apoptosis

Abstract: We have previously described the marine toxin okadaic acid (OKA) to be a potent neurotoxin for cultured rat cerebeHar neurons. Here we show that OKA-induced neurodegeneration involves the DNA fragmentation characteristic of apoptosis and is protein synthesis-dependent. DNA fragmentation and neurotoxicity correlated with inhibition of protein phosphatase (PP) 2A rather than PP1 activity. Neurotrophins NT-3 and BDNF failed to protect from OKA-induced apoptotic neurotoxicity that was, however, totally prevented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 45 publications
(66 reference statements)
6
22
0
Order By: Relevance
“…Although we did not address the issue of an involvement of phosphatases in our model, okadaic acid (OA), a serine/threonine phosphatase inhibitor has been demonstrated to induce death of CGNs and hippocampal neurons (Fernandez-Sanchez et al, 1996;Runden et al, 1998). In hippocampal neurons, OAinduced cell death is accompanied by sustained activation of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not address the issue of an involvement of phosphatases in our model, okadaic acid (OA), a serine/threonine phosphatase inhibitor has been demonstrated to induce death of CGNs and hippocampal neurons (Fernandez-Sanchez et al, 1996;Runden et al, 1998). In hippocampal neurons, OAinduced cell death is accompanied by sustained activation of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent report [54], FernandezSanchez et al suggested that in primary cultures of rat cerebellar granule neurons, inhibition of PP-2A but not PP-1 leads to apoptosis since 5 nM but not 100 nM okadaic acid induces DNA fragmentation. In both cases, however, it was not determined whether 100 µM microcystin can actually inhibit PP-1 or whether 5 nM okadaic acid can inhibit PP-2A [48,54]. We briefly reported that PP-1 is important in regulating the apoptotic program in the lens system [71].…”
Section: Discussionmentioning
confidence: 99%
“…PP-1 promotes survival through regulation of p53 and other targets It has been well documented that inhibition of PP-1 or/and PP-2A by the marine algae toxins, okadaic acid and calyculin A, induces apoptosis of various types of cells (Boe et al, 1991;Ishida et al, 1992;Mellgren et al, 1993;Kiguchi et al, 1994;Weller et al, 1995;Fernandez-Sanchez et al, 1996;Morana et al, 1996;Sheikh et al, 1996;Yan et al, 1997;Li et al, 1998Li et al, , 2001aGarcia et al, 2003). However, why inhibition of PP-1 or/and PP-2A leads to apoptosis remains largely unknown.…”
Section: Dephosphorylation Of P53 Displays Strong Impact On Its Functmentioning
confidence: 99%